Associations Between Oral Health Status, Perceived Stress, and Neuropsychiatric Symptoms Among Community Individuals With Alzheimer's Disease: A Mediation Analysis - Yang, Bing; Tao, Binbin; Yin, Qianyu; Chai, Zhaowu; Xu, Ling; Zhao, Qinghua; Wang, Jun (Frontiers in Aging Neuroscience, 2022)
Community individuals with Alzheimer's disease (AD) experience oral disease alongside neuropsychiatric symptoms (NPS) with disease progression. Despite growing evidence for the link between oral health and cognitive status, few studies have investigated the associations between oral health and NPS, especially based on individuals' experience of AD. The primary aim of this study was to examine (a) the difference in oral health-related stressors among individuals with AD, mild cognitive impairment (MCI), and subjective cognitive decline (SCD); and (b) the associations of these stressors with NPS under the framework of the stress process model (SPM). A cross-sectional study was conducted among individuals diagnosed with AD (n = 35), MCI (n = 36) or SCD (n = 35), matched for age, sex education, and body mass index (BMI). Multiple regression and mediation model analyses were performed to explore predictors and their relationships with NPS based on the SPM. Data collection comprised four sections: (a) individual context; (b) oral health-related stressors, including dental caries, periodontal status, oral hygiene, the geriatric oral health assessment index (GOHAI), oral salivary microbiota, pro-inflammatory cytokines, and oral health behavior; (c) subjective stressors (i.e., perceived stress [PS]); and (d) NPS. Decayed, missing, and filled teeth (DMFT), missing teeth (MT), loss of attachment (LoA), plaque index (PLI), PS, oral health behavior, GOHAI, pro-inflammatory cytokines, and salivary bacterial composition were significantly different among the three groups; these parameters were poorer in the AD group than SCD and/or MCI group. LoA, PLI, PS, and pain or discomfort in the GOHAI were directly associated with NPS. PLI, LoA, and psychosocial function in the GOHAI indirectly affected NPS, and this relationship was mediated by PS. Individuals with AD reported greater oral health-related stressors. This study identifies direct and indirect associations linking oral health-related stressors and PS with NPS in individuals with AD. Our findings suggest that targeted dental care and oral-related stressor control may be valuable for managing NPS.